Protein Localization at Mitochondria-ER Contact Sites in Basal and Stress Conditions - Ilacqua, Nicolò; Sánchez-Álvarez, Miguel; Bachmann, Magdalena; Costiniti, Veronica; Del Pozo, Miguel A.; Giacomello, Marta (Frontiers in Cell and Developmental Biology, 2017)
Mitochondria-endoplasmic reticulum (ER) contacts (MERCs) are sites at which the outer mitochondria membrane and the Endoplasmic Reticulum surface run in parallel at a constant distance. The juxtaposition between these organelles determines several intracellular processes such as, to name a few, Ca2+ and lipid homeostasis or autophagy. These specific tasks can be exploited thanks to the enrichment (or re-localization) of dedicated proteins at these interfaces. Recent proteomic studies highlight the tissue specific composition of MERCs, but the overall mechanisms that control MERCs plasticity remains unclear. Understanding how proteins are targeted at these sites seems pivotal to clarify such contextual function of MERCs. This review aims to summarize the current knowledge on protein localization at MERCs and the possible contribution of the mislocalization of MERCs components to human disorders.